Vega: An academic publishing system for the 21st century - Ball, Cheryl E. (Septentrio Conference Series, 2018)
Watch the VIDEO. Vega is a new, open-source academic publishing system, built as a collaboration between US-based library publishers and an Oslo-based design studio, Sanity (nee Bengler). Vega was built with a 1m Andrew W. Mellon Foundation grant to fill a need in academic publishing for open-source, easy-to-use editorial management system that could highlight the publication of multimedia artifacts in a born-digital publishing workflow. Vega facilitates authoring, editing, and publishing academic content as reusable structured data and facilitates innovation in indexing and presentation of this content. This short presentation will focus on the design goals underpinning Vega, specifically the goal of providing an intuitive, scholar-friendly way of editing academic documents as semantically clear, structured data while also featuring the inclusion of multimedia assets as part of the scholarly record. The Vega publishing platform incorporates collaborative digital authoring and editing platforms and a fully customizable front end for a branded reader experience. Vega is built on an open source data store and includes strong, yet flexible, editorial workflows that train editors in digital publishing best practices, especially with multimedia. For instance, the editorial dashboard features peer review options for different tracks/sections in publications, including the traditional double anonymous review process as well as collaborative reviews and fully open peer reviews, depending on each venue's and each text's needs. The UX in Vega also allows editors to see what's going on in their venues at a glance – through a visualization that tracks each text in each stage of the editorial and production process and allows for editors to engage directly with that text with a double click regardless of where it is in the process. This presentation will highlight how Vega facilitates multiple workflows for multimodal publications (i.e. pdf, website, data, interactive experience), and how it facilitates archivability and indexability. Vega will change the scholarly communications landscape and is now available for use through free download or hosting options.